2019
DOI: 10.1161/strokeaha.118.023392
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Target Mismatch Profile >24 Hours After Stroke Onset in DEFUSE 3

Abstract: Background and Purpose— Efficacy of endovascular thrombectomy has been demonstrated up to 24 hours after stroke onset in patients selected with perfusion imaging. We hypothesized that a persistent favorable perfusion profile exists in some patients beyond 24 hours from the onset and can be predicted by a lower baseline hypoperfusion intensity ratio, which indicates favorable collaterals. Methods— We identified control arm patients from the DEFUSE 3 tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 10 publications
1
52
0
1
Order By: Relevance
“…We would draw attention to our recent publication that examined imaging profiles 24 hours after randomization in the DEFUSE 3 study. 3 This study found that approximately 20% of patients retain a Target Mismatch 24 hours after enrollment, which indicates that robust collaterals can persist for prolonged periods of time. 3 As we said in our article, "until we better understand collateral evolution, we will not fully appreciate their effect on neurological outcome or comprehend how to therapeutically modify that effect."…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…We would draw attention to our recent publication that examined imaging profiles 24 hours after randomization in the DEFUSE 3 study. 3 This study found that approximately 20% of patients retain a Target Mismatch 24 hours after enrollment, which indicates that robust collaterals can persist for prolonged periods of time. 3 As we said in our article, "until we better understand collateral evolution, we will not fully appreciate their effect on neurological outcome or comprehend how to therapeutically modify that effect."…”
mentioning
confidence: 75%
“…3 This study found that approximately 20% of patients retain a Target Mismatch 24 hours after enrollment, which indicates that robust collaterals can persist for prolonged periods of time. 3 As we said in our article, "until we better understand collateral evolution, we will not fully appreciate their effect on neurological outcome or comprehend how to therapeutically modify that effect." Additional research is needed, with follow-up imaging at time points past 24 or 48 hours from last known normal, to validate or refute the findings of this analysis and, more importantly, to provide a viable pathway forward for translational collateral research.…”
mentioning
confidence: 75%
“…A significant number of patients presenting in the extended window do not have favorable imaging profile 35 . Moreover, those with favorable profile (slow progressors), become ineligible for treatment if not recanalized immediately after onset and develop extensive infarction leading to poor outcomes 36,37 . Patient presenting with favorable penumbral pattern on imaging should receive thrombectomy expeditiously with careful monitoring of imaging‐to‐skin puncture and imaging‐to‐recanalization time metrics.…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference in the rate of symptomatic intracranial haemorrhage (5% vs 6%, p=0.87) or of good outcome (90 day mRS score of 0–2, 43% vs 48%, p=0.68) when compared with the intervention arm patients 1. This study together with data from DEFUSE 3 suggest that intervention for patients with large intracranial vessel occlusion presenting beyond 24 hours is justified on an individualised basis 1 2. The decision to proceed with off-label treatment in our patient was also based on MRI demonstration of viable symptomatic brain tissue despite established insular infarction and the likely eventual demise of eloquent penumbral tissue.…”
mentioning
confidence: 65%
“…In two patients, the follow-up imaging at 4 days from stroke onset showed progression of expansion of infarct core; both had poor outcomes. One patient (10%) had a good outcome (modified Rankin Scale (mRS) score of 0–1) and most (60%) were dead or severely disabled (mRS score 5–6) at 90 days, probably reflecting progressive penumbral demise and infarct core expansion without reperfusion 2…”
mentioning
confidence: 99%